Developing a conceptual framework for the co-operative and mutual enterprise business model. (11th June 2018) - Mazzarol, Tim; Clark, Delwyn; Reboud, Sophie; Mamouni Limnios, Elena
Abstract: The co-operative and mutual enterprise business model represents a unique type of organisation that has a dual purpose focused on both economic and social goals. For nearly two centuries it has played an important role in economic development, job creation and addressing market failures. However, despite its potential importance to economic development it has been largely ignored within the mainstream economics and management literature. This paper provides an overview of the nature of the co-operative and mutual enterprise business model and also proposes a business model framework or 'canvas' that can be used for research, teaching and strategic analysis.